Visceral leishmaniasis in the hills of western Nepal: A transmission assessment. - Surendra Uranw; Narayan Raj Bhattarai; Kristien Cloots; Lalita Roy; Keshav Rai; Usha Kiran; Uttam Raj Pyakurel; Bibek Kumar Lal; Sakib Burza; Suman Rijal; Prahlad Karki; Basudha Khanal; et al. (PLoS ONE)
In Nepal, visceral leishmaniasis (VL) has been targeted for elimination as a public health problem by 2026. Recently, increasing numbers of VL cases have been reported from districts of doubtful endemicity including hills and mountains, threatening the ongoing VL elimination program in Nepal. We conducted a multi-disciplinary, descriptive cross-sectional survey to assess the local transmission of Leishmania donovani in seven such districts situated at altitudes of up to 1,764 meters in western Nepal from March to December 2019. House-to-house surveys were performed for socio-demographic data and data on past and current VL cases. Venous blood was collected from all consenting individuals aged ≥2 years and tested with the rK39 RDT. Blood samples were also tested with direct agglutination test, and a titer of ≥1:1600 was taken as a marker of infection. A Leishmania donovani species-specific PCR (SSU-rDNA) was performed for parasite species confirmation. We also captured sand flies using CDC light traps and mouth aspirators. The house-to-house surveys documented 28 past and six new VL cases of which 82% (28/34) were without travel exposure. Overall, 4.1% (54/1320) of healthy participants tested positive for L. donovani on at least one serological or molecular test. Among asymptomatic individuals, 17% (9/54) were household contacts of past VL cases, compared to 0.5% (6/1266) among non-infected individuals. Phlebotomus argentipes, the vector of L. donovani, was found in all districts except in Bajura. L. donovani was confirmed in two asymptomatic individuals and one pool of sand flies of Phlebotomus (Adlerius) sp. We found epidemiological and entomological evidence for local transmission of L. donovani in areas previously considered as non-endemic for VL. The national VL elimination program should revise the endemicity status of these districts and extend surveillance and control activities to curb further transmission of the disease.